2009
DOI: 10.1099/vir.0.011841-0
|View full text |Cite
|
Sign up to set email alerts
|

Second-site mutations in Borna disease virus overexpressing viral accessory protein X

Abstract: The X protein of Borna disease virus (BDV) is an essential factor that regulates viral polymerase activity and inhibits apoptosis of persistently infected cells. We observed that a BDV mutant which carries an additional X gene replicated well in cell culture only after acquiring second-site mutations that selectively reduced expression of the endogenous X gene. In rat brains, the virus acquired additional mutations which inactivated the ectopic X gene or altered the sequence of X. These results demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Structure modelling ( Supplementary Fig. 2) predicts a highly disordered protein, except for a short N-terminal aliphatic alpha helix, that carries both nuclear and mitochondrial localization domains 27 . Thus, we synthesized three peptides covering the entire amino-acid sequence of the X protein to test each of them separately for neuroprotection (Fig.…”
Section: Articlementioning
confidence: 99%
“…Structure modelling ( Supplementary Fig. 2) predicts a highly disordered protein, except for a short N-terminal aliphatic alpha helix, that carries both nuclear and mitochondrial localization domains 27 . Thus, we synthesized three peptides covering the entire amino-acid sequence of the X protein to test each of them separately for neuroprotection (Fig.…”
Section: Articlementioning
confidence: 99%
“…These findings clearly suggest that downregulation of GFP expression occurred at the level of transcription. Insertion of additional A nucleotides into the UA 7 termination motif might interfere with efficient recognition of the termination signal as previously postulated (10). Northern blot analysis of GFP expression 10 weeks p.i.…”
mentioning
confidence: 99%
“…Only a minor population of cell somata showed a clear costaining for GFP and nucleoprotein N (yellow cell body and green dendrites), indicating the existence of a population of mBDV-GFP viruses with severely reduced GFP expression capacities. We recently demonstrated that BDV is able to downregulate transcription of an ectopic X gene by modification of the transcription termination/initiation signals directly upstream of the inserted gene (10). To analyze whether similar mechanisms were responsible for the downregulation of GFP expression in mice, we isolated RNA from the brains of mice sacrificed 4 and 10 weeks after infection with mBDV-GFP and amplified by reverse transcription-PCR (RT-PCR) the complete GFP gene, including the upstream sequences that regulate termination and reinitiation of transcription (Fig.…”
mentioning
confidence: 99%